Expression and significance of PD-1 and PD-L1 in patients with recurrent spontaneous abortion: A protocol for systematic review and meta-analysis. Issue 14 (9th April 2021) - Li, Tao; Chen, Yihong; Lai, Yi; He, Guoqian; He, Guolin
Abstract: Background: Recurrent spontaneous abortion (RSA) accounts for the most common complication of early pregnancy in humans. As an immune checkpoint pathway, programmed death-1 (PD-1) and programmed death ligand-1 (PD-L1) can be exploited by tumor cells to evade immuno-surveillance. Many studies have shown that the expression of PD-1/PD-L1 is involved in RSA. However, the correlation between the expression of PD-1/PD-L1 and RSA is still controversial. We conducted meta-analysis to further explore the correlation between the expression of PD-1/PD-L1 and RSA, to provide a basis for clinical prevention and treatment. Methods: We will search PubMed, Embase, Web of Science, Google Scholar, Chinese National Knowledge Infrastructure, Chinese VIP Information, Wanfang Database, and Chinese Biomedical Literature Database for related published studies before February 2021. Two review authors will search and assess relevant studies independently. Case control studies and cohort studies will be included. The Revman 5.3 software was applied to carry out the meta-analysis for the included literature. Results: The findings of this systematic review will be disseminated in a peer-reviewed publication and/or presented at relevant conferences. Conclusion: This study will provide a new theoretical basis for the prevention and treatment of RSA. Trial registration number: DOI 10.17605/OSF.IO/CZD23. Ethics and dissemination: Formal ethical approval is not required, as the data are not individualized.